Individual Interest in E-Wallet Go-pay Transactions As Payment Services (Study on Students of Economics and Business Faculty of State Univeristies in Malang City) - Ayunda Deica Budia Putri (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2019)
In this era of globalization, the development of information and technology causes somechanges in economic system, in particular the method of payment. This study aims to examinethe interest of individuals in making payments through e-wallet by using seven constructsadopted from the Technology Acceptance Model (TAM) namely: perceived usefulness,perceived ease of use, attitudes, perceived security, individual intention to use behavior; oneconstruct from the Unified Theory of Acceptance and Use of Technology (UTAUT), namelysocial influence; and one construct of trust that is trust in e-wallet. Through a quantitativeapproach and data acquisition techniques using survey methods, this study examined 240students from economics and business faculty of state universities student in Malang City. Theresults of this study indicate that attitude, social influence, perceived security and trust have apositive effect towards individual’s intention to use e-wallet Go-pay and intention to use havepositive effect towards use behavior. Furthermore, perceived usefulness and perceived ease ofuse also have positive effect towards attitude. On the other hand, informal learning has nopositive effect towards individual’s intention to use e-wallet Go-pay. The results of this studyare expected to provide input to the e-wallet company application services to pay attention tothe features that related to the usage behavior, usage benefit, ease of use, security, trust andsocial influence for developing and marketing e-wallet Go-pay products. It is because thefeatures are proven to be able to attract consumers to use e-wallet application such as Go-pay. Keywords: Attitude, Intention to Use, Use Behavior, Perceived Usefulness, Perceived Ease ofUse, Social influence, Perceived Security, Trust, Informal Learning.